DETERMINAN KUALITAS LAYANAN INTERNET BANKING DENGAN MENGGUNAKAN METODE WEBQUAL VERSI 4.0 DAN PENGARUHNYA TERHADAP KEPUASAN NASABAH TOP BRAND E-CHANNEL BANK DI INDONESIA - Wardhana, Aditya (IMAGE : Jurnal Riset Manajemen, 2015)
Research aim was to assess the influence of the quality of services e-channel (internet banking) determinants by using the method webqual version 4.0 against satisfaction customers top brand e-hannel banks in Indonesia. They were bank BCA, bank Mandiri bank BRI, and bank BNI. The population of this study were bank customers form BCA, bank Mandiri, bank BRI, and bank BNI who used the internet banking as 17.797.523 customers by the size of samples as 400 respondents. The sampling method used nonprobability sampling by incidental sampling. The results of research showed by using regression analysis that the quality of services e-channel (internet banking) determinants (which included the usability, quality information, and interaction of quality) contributed and influenced in a partial and simultaneous significantly to the satisfaction of customers in using internet banking services by 81 % of the remaining 19 % described by other variables that not investigated in this research.